Resistance to Change in Software Process Improvement - An Investigation of Causes, Effects and Conducts - Anastassiu, Monica; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Context:Resistance to change can affect the effectiveness of software process improvement initiatives as well as the maintenance of improvements after an official assessment. However, the inherent attributes of resistance to change are not entirely clear, for instance: its effects as well as actions to mitigate its occurrence. Objective: We aim to investigate potential causes and effects of resistance to change as well as conducts that can mitigate its occurrence on software processes improvement initiatives. Method: We performed a qualitative study in which we interviewed 21 practitioners and specialists in software process improvement. Results: We have identified 32 causes, 16 effects, and 29 conducts related to resistance to change. For instance, resistant senior management can sabotage the process by creating resistance to other stakeholders who want to implement improvements. Conclusion: We found that resistance to change in software process improvement initiatives also includes resistance to follow the processes. A significant part of the conducts comprises preventive and low-cost actions. Additionally, the results pointed out situations in which given conduct to mitigate resistance can generate other positive impacts like collaborative work fostering continuous improvements. Also, we observed that individuals are more affected by resistance to change than the projects. Our findings and their interconnections expose a diverse set of circumstances that can be explored to help achieve the objectives of a software process improvement initiative.